2000
DOI: 10.1046/j.1468-0734.2000.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Cells, Cytokine Loops and Cell‐to‐Cell Interactions in Chronic Lymphocytic Leukemia

Abstract: In addition to the extensive work that has been conducted in order to understand better the biological features of the leukemic population in B-cell chronic lymphocytic leukemia (CLL), over the years considerable interest has been directed towards other related studies that may have important implications for the accumulation of the leukemic clone and for the immunoparesis typical of this disease. In the present review article, we discuss some of these areas of investigation and, in particular, we focus on: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
3

Year Published

2001
2001
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 140 publications
0
8
0
3
Order By: Relevance
“…This is a pleiotropic cytokine produced by macrophages, B lymphocytes and natural killer cells. B-CLL cells are shown to express TNF-α mRNA and secrete spontaneously TNF-α in vitro [12, 13]. Our study revealed significantly higher levels of serum TNF-α in anemic compared to nonanemic patients, and an inverse correlation between TNF-α concentration and hemoglobin level.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This is a pleiotropic cytokine produced by macrophages, B lymphocytes and natural killer cells. B-CLL cells are shown to express TNF-α mRNA and secrete spontaneously TNF-α in vitro [12, 13]. Our study revealed significantly higher levels of serum TNF-α in anemic compared to nonanemic patients, and an inverse correlation between TNF-α concentration and hemoglobin level.…”
Section: Discussionmentioning
confidence: 56%
“…B-CLL cells are capable of spontaneously secreting increased amounts of TNF-α in vitro [12, 13]. Moreover, elevated serum TNF-α levels have been observed in CLL patients [7, 14], and have been associated with anemia and shorter survival [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, B-CLL cells express high levels of Fas ligand and may induce the apoptotic death of plasma cells, with subsequent hypogammaglobulinemia (32). B-CLL cells also live in protected niches, resulting in a markedly reduced apoptotic rate due to a microenvironment high in tumor necrosis factor-a, IL-4, and IL-8, all of which have an antiapoptotic effect on B-CLL cells (33,34). All of these factors act during the induction phase of the immune response and may not be as important in B-CLL as thought previously, because patients with this disease retain the capacity to generate an antitumor immune response as indicated by the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the recirculation process of CLL cells from blood to lymphoid tissues might be crucial for CLL cells accumulation and survival and highlights the predominant role of the tumor microenvironment in the pathogenesis of CLL (3,4). CLL microenvironment contains several cytokines acting through autocrine/paracrine mechanisms to affect CLL cell survival, migration, and resistance to drug-induced apoptosis (5,6). Among them, the CXCL12 chemokine and its receptor CXCR4 seem to play an important role for homing of CLL cells into the bone marrow but also for CLL cell survival through cell-to-cell contacts with marrow stromal and/or nurselike cells (7)(8)(9).…”
Section: Introductionmentioning
confidence: 97%